Modelling whale-vessel encounters: the role of speed in mitigating collisions with humpback whales (Megaptera novaeangliae) - Currie, J. J.; Stack, S. H.; Kaufman, G. D. (J. Cetacean Res. Manage., 2023)
Increasing whale populations and vessel traffic worldwide has led to an increase in reported whale-vessel collisions. This paper reports on factors that affect the rate of whale-vessel collisions in the four-island region of Maui, Hawai’i. More specifically, it aims at quantifying the probability of a whale-vessel collision with varying vessel speeds using encounter distances as a proxy. A change point model was used to identify a speed threshold of 12.5kts (6.4m/s), which showed a significant change in the relationship between speed and mean sighting distance. A 3.4-fold decrease in close encounters with humpback whales was observed when vessels travelled at speeds of 12.5kts (6.4m/s) or less. Furthermore, results indicate that lone adult whales and calves are the most likely to be involved in a collision. A speed limit of 12.5kts (6.4m/s) is warranted in areas and/or during seasons where a high density of whales occurs. This limit aligns with a reduction in lethal vessel strikes with speed from previous studies which found a significant increase in the likelihood of mortality when vessel speed exceeds 12kts.